Behavioural Component in the Development of the Moral Culture among Preschool Children - Abylaikha, Saltanat M.; Karmanova, Zhanat A.; Konkhashova, Ulzhan M.; Iskakova, Maral B.; Nursulankyzy, Aikerim (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The relevance of the study is defined by the need to identify the current moral level of pre-schoolers, to identify factors that positively and negatively affect the moral culture of the child, as well as to develop a methodological foundation for the effective and controlled development of moral culture, ethical principles and empathy among children of 4-5 years old considering the behavioural component. This study focuses on assessing the real levels of moral and cultural development among children, their systematisation and analysis, and making recommendations for teachers and parents to develop moral qualities in a child. The leading method for studying this problem is an experimental method that enables a comprehensive assessment of the moral culture among preschool children. In addition, methods such as structural analysis, comparative method, statistical method, synthesis and deduction methods, and the method of classification were used in the study. The study presents the results of an experiment to establish the level of development of the behavioural component of moral culture among preschool children, reveals the weaknesses of the development of this component, identifies methods of pedagogical influence on the development of moral culture, and makes recommendations for activities, pedagogical methods, and techniques that can be used to make a predictable positive impact on the moral culture of the child. The study materials are of practical value for teachers of preschool educational institutions, child psychologists, as well as teachers and students of pedagogical programmes, and parents.